(No ROMANTI^ESKOJ PO\TIKE W TWOR^ESTW dEB@SSIs (NMONOGRAFIQs - (Nr(B. (NkUNICKAQs ((NmOSKWAs (NmUZYKAs, 1982)
(NkNIGA SODERVIT ISTORIKO(B-(NSTILISTI^ESKIJ ANALIZ(B,(NWOKALXNYH(B,(NINSTRUMENTALXNYH SO^INENIJ(B,(NOPERY pELLE^ESKIE ^ERTY HUDOVESTWENNOGO MY[LENIQ KOMPOZITORA(B.s
Keywords: (NMONOGRAFIQs